A virtual chromoendoscopy artificial intelligence system to detect endoscopic and histologic activity/remission and predict clinical outcomes in ulcerative colitis - Iacucci, Marietta; Cannatelli, Rosanna; Parigi, Tommaso L.; Nardone, Olga M.; Tontini, Gian Eugenio; Labarile, Nunzia; Buda, Andrea; Rimondi, Alessandro; Bazarova, Alina; Bisschops, Raf; del Amor, Rocio; Meseguer, Pablo; Naranjo, Valery; Ghosh, Subrata; Grisan, Enrico; on behalf of the PICaSSO group; Bhandari, Pradeep; de Hertogh, Gert; Ferraz, Jose G.; Goetz, Martin; Gui, Xianyong; Hayee, Bu'Hussian; Kiesslich, Ralf; Metelli, Chiara; Lazarev, Mark; Panaccione, Remo; Parra-Blanco, Adolfo; Pastorelli, Luca; Rath, Timo; Røyset, Elin Synnøve; Vieth, Michael; Villanacci, Vincenzo; Zardo, Davide (Endoscopy, 2022)
Background Endoscopic and histological remission (ER, HR) are therapeutic targets in ulcerative colitis (UC). Virtual chromoendoscopy (VCE) improves endoscopic assessment and the prediction of histology; however, interobserver variability limits standardized endoscopic assessment. We aimed to develop an artificial intelligence (AI) tool to distinguish ER/activity, and predict histology and risk of flare from white-light endoscopy (WLE) and VCE videos.Methods 1090 endoscopic videos (67 280 frames) from 283 patients were used to develop a convolutional neural network (CNN). UC endoscopic activity was graded by experts using the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) and Paddington International virtual ChromoendoScopy ScOre (PICaSSO). The CNN was trained to distinguish ER/activity on endoscopy videos, and retrained to predict HR/activity, defined according to multiple indices, and predict outcome; CNN and human agreement was measured.Results The AI system detected ER (UCEIS ≤ 1) in WLE videos with 72 % sensitivity, 87 % specificity, and an area under the receiver operating characteristic curve (AUROC) of 0.85; for detection of ER in VCE videos (PICaSSO ≤ 3), the sensitivity was 79 %, specificity 95 %, and the AUROC 0.94. The prediction of HR was similar between WLE and VCE videos (accuracies ranging from 80 % to 85 %). The model’s stratification of risk of flare was similar to that of physician-assessed endoscopy scores. Conclusions Our system accurately distinguished ER/activity and predicted HR and clinical outcome from colonoscopy videos. This is the first computer model developed to detect inflammation/healing on VCE using the PICaSSO and the first computer tool to provide endoscopic, histologic, and clinical assessment.